TANGGUNG JAWAB HUKUM DIREKSI TERHADAP KERUGIAN PERUSAHAAN DALAM PENGURUSAN PERSEROAN TERBATAS - Purbo Adjar Waskito (CITA HUKUM INDONESIA, 2022)
The Board of Directors as the organ of the PT is to represent the interests of the PT as an independent legal subject. This is because PT is the cause of the existence (raison d'etre) of the board of directors, because if there is no PT, then the board of directors will never exist. The problems that will be examined are 1. Why do losses occur in the company due to the management of PT?, 2. What is the role of the Board of Directors in managing company losses in the management of a limited liability company? The research method used is normative juridical. The occurrence of losses in the management of PT is caused by froud carried out by the directors, Fraudulent Financial Reporting, Company errors, the Company does not yet have legal instruments in the form of work management. Abuse of Authority of the Board of Directors. The role of the Board of Directors on company losses in managing a limited liability company as described and described, their duties as management of the company have the authority determined and limited by: 1. Legal provisions (Law No. 40 of 2007 and other related laws); 2. Company's Articles of Association; 3. GMS (General Meeting of Shareholders); 4. The “Ultra Virres” Doctrine; 5. Fiduciary Duty Principle. A Director who acts outside the provisions and limitations above, means that he has departed from the legal principle of representation and is qualified to have committed an act of abuse of authority